(untitled) (KYAMC Journal, 2018)
CA-125 (cancer antigen 125, carcinoma antigen 125, or carbohydrate antigen 125) also known as mucin 16 or MUC16 is a protein of mucin family glycoprotein that is encoded by the MUC16 gene. It is the most frequently used biomarker for ovarian cancer. It may also be elevated in other cancers, including endometrium, fallopian tube, lung, breast and gastrointestinal cancer and in a number of relatively benign conditions, such as endometriosis, menstruation and pregnancy. High plasma levels of more than 200 U/mL are usually suggestive of malignancy but rarely found in benign conditions of female genital tract, like endometriosis. Very high CA- 125 level is suggestive of ovarian malignancy, was noted in case of ovarian endometrioma. This paper describes a case of a 36 years old lady, mother of 2 children, was admitted with large abdominal mass and abdominal pain. CA-125 was found 3500 U/ML. Ovarian malignancy was suspected. During laparotomy, ruptured endometrioma was noted and it was supported by histopathological report which mentioned," No malignancy seen". Endometrioma can’t be excluded in high CA-125 level even without features of endometriosis. KYAMC Journal Vol. 9, No.-3, October 2018, Page 139-140